Methabolic reaction on the cerebral ischemia during carotid artery surgery - M.A. Stupnytskyi; M.V. Syroyid; O.I. Dumchenko; N.V. Denysenko; Yu.M. Fedevych (Medičnì Perspektivi, 2023)
One of the ischemic stroke prevention methods is reconstructive surgery on the carotid arteries, during which there is a risk of ischemia-reperfusion phenomenon. Nevertheless, there is still a high risk of stroke at all stages of the surgery, which equally depends on the atherosclerotic plaque structure and on the technique and tactics of surgery. The aim of this study was to investigate the dynamics of redox homeostasis and nitric oxide production in the blood taken from the internal jugular vein in patients with carotid arteries pathology against the episode of cerebral blood flow restriction during carotid surgery. This prospective cohort study involved 56 patients which required carotid reconstructive surgery. The markers dynamics of oxygen metabolism, redox homeostasis and nitric oxide production in blood from the internal jugular vein on the side of surgery were studied. It was found that the activity of free radical processes is proportional to the level of jugular hypoxemia. Bidirectional dynamics of lactate concentration during intraoperative transient cerebral ischemia was revealed. In some patients, lactate production activates with an increase in free radical processes activity in proportion to the intensification of nitric oxide synthesis against a decrease in peroxynitrite production and activation of molecular compensatory mechanisms increasing concentrations of L-arginine and reduced glutathione. In others, the extraction of oxygen from the blood increases without lactate production, activation of nitric oxide synthesis and development of oxidative stress. This indicates good adaptive reserves against acute restriction of cerebral blood flow.